Efficiency of a combined system for the removal of organic load from dairy effluents - Apaza-Aquino, Hugo (2021)
One of the main residues generated in the dairy industry is whey, due to its high organic load it represents a serious environmental problem when it is disposed of to receiving natural bodies, altering its environmental quality. The efficiency of a combined system composed of electrocoagulation and biological filter was evaluated; for which the electrocoagulation process was carried out in a batch reactor with aluminum and iron electrodes, the biological filter was packed with biomass composed of: Bacillus spp, Acinetobacter spp, Lactobacillus spp and Streptococcus spp. Electrocoagulation was responsible for reducing the organic load by more than 80% and the biological filter working with an average organic load of 1405 mg / L of BOD5 contributed to the reduction of the remaining organic load; the combined electrocoagulation-biological filter system with recirculation achieved a removal efficiency for COD of 89.7% and for BOD5 of 89.8%, with a final pH of 7.37. There are various technologies to treat wastewater from the dairy industry, but the application of a combined system could be an alternative to treat dairy wastewater due to the efficiency obtained.